2014
DOI: 10.5114/pr.2014.46049
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 concentrations in the internal jugular and azygous veins in multiple sclerosis patients: the results of a pilot study

Abstract: Objectives: In this pilot study we examined the potent vasoconstrictor, endothelin-1, in the blood of multiple sclerosis patients in the context of chronic cerebrospinal venous insufficiency hypothesis. For this purpose we measured endothelin-1 concentrations in blood samples that were obtained during selective catheterisation of the main veins draining the central nervous system: the internal jugular veins and the azygous vein. Material and methods:We measured endothelin-1 concentrations in peripheral blood i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…It is also likely that local stasis of blood in abnormal extracranial veins could be responsible. Also, it was possible that hypercapnia and hypoxaemia in blood samples drawn from the internal jugular veins were partially caused by asymmetric venous outflow from the brain [16,19,20]. Still, the studies utilising perfusion MRI have shown that MS patients exhibit significant hypoperfusion of the brain [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that local stasis of blood in abnormal extracranial veins could be responsible. Also, it was possible that hypercapnia and hypoxaemia in blood samples drawn from the internal jugular veins were partially caused by asymmetric venous outflow from the brain [16,19,20]. Still, the studies utilising perfusion MRI have shown that MS patients exhibit significant hypoperfusion of the brain [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%